Long-Term Valproate Hematologic Side Effects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Hematologic side effects in 60 patients, aged 2-29 years (mean 14 years), receiving valproate (VPA) monotherapy for >4 years in a long-term care facility, are reported from the Department of Pediatrics, East Carolina University School of Medicine, Greenville, North Carolina.